Freud and the post-Freudians - Brown, J. A. C. (James Alexander Campbell) 1911-1964 (Penguin Books Ltd, 1961)
Brief account of main concepts of Freudian, Neo-Freudian and Post-Freudian schools of psychology, presenting theories of Adler, Jung, Horney, Fromm, Sullivan and others. For other editions, see Author Catalog.